Eugenia polyantha leaf extract as an antidiabetic alternative medicine on Rattus norvegicus - Waluyo, Joko; Fikri, Kamalia; Cahyani, Fadhila Siti (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2023)
The public does not yet know the potential of Eugenia polyantha as an alternative medicine for diabetes mellitus. In fact, the content of chemical compounds such as flavonoids in Eugenia polyantha can minimize damage to the pancreas. This study aimed to determine the antidiabetic activity of the ethanolic extract of Eugenia polyantha leaf against streptozotocin-induced Wistar rats. The sample for this study were male white rats of the Wistar strain, consisting of 30 rats. It was divided into 6 test groups, group P1 was negative control (aqua dest), group P2 was positive control (glibenclamide), and group P3, P4, and P5 was treated with 70% ethanol extract of Eugenia polyantha leaf with doses of 312.5, 625 and 1250 mg/kg respectively. The blood glucose level on the 11th day was tested by ANOVA which is then tested by Duncan. The results showed Eugenia polyantha leaf extract has an effect on reducing blood glucose in Wistar rats (Rattus norvegicus) with doses 312.5, 625, and 1250 mg/kg body weight. The most effective dose of 70% ethanol extract of Eugenia polyantha leaf for reducing blood glucose is 1250 mg/kg body weight. Furthermore, the findings of this study can be tested in more depth so that it can be recommended to the public as an alternative medicine for diabetes mellitus in humans.